The Affordable Care Act and Cancer Care for Young Adults. Issue 3 (May 2017) - Han, Xuesong; Jemal, Ahmedin
Abstract : Abstract: The Affordable Care Act (ACA) requires health plans that provide coverage for dependents to cover adult children to age 26 years. Extensive evidence has shown that since its implementation in September 2010 insurance coverage and access to care for young adults in the general population have increased. This article reviews the studies that have evaluated the impacts of the ACA on access to cancer care and outcomes for young adults aged 19 to 25 years. Current literature shows that the ACA increased insurance rate and cancer diagnosis at early stage for young adults. There is also evidence of the ACA's positive effects on initiation and completion of human papillomavirus vaccination and receipt of fertility-sparing treatment for cervical cancer among young women. Several avenues of future research on the ACA and cancer care are suggested.